Lamin A/C Mechanosensor Drives Tumor Cell Aggressiveness and Adhesion on Substrates With Tissue-Specific Elasticity - Urciuoli, Enrica; D’Oria, Valentina; Petrini, Stefania; Peruzzi, Barbara (Frontiers in Cell and Developmental Biology, 2021)
Besides its structural properties in the nucleoskeleton, Lamin A/C is a mechanosensor protein involved in perceiving the elasticity of the extracellular matrix. In this study we provide evidence about Lamin A/C-mediated regulation of osteosarcoma cell adhesion and spreading on substrates with tissue-specific elasticities. Our working hypothesis is based on the observation that low-aggressive and bone-resident SaOS-2 osteosarcoma cells express high level of Lamin A/C in comparison to highly metastatic, preferentially to the lung, osteosarcoma 143B cells, thereby suggesting a role for Lamin A/C in tumor cell tropism. Specifically, LMNA gene over-expression in 143B cells induced a reduction in tumor cell aggressiveness in comparison to parental cells, with decreased proliferation rate and reduced migration capability. Furthermore, LMNA reintegration into 143B cells changed the adhesion properties of tumor cells, from a preferential tropism toward the 1.5 kPa PDMS substrate (resembling normal lung parenchyma) to the 28 kPa (resembling pre-mineralized bone osteoid matrix). Our study suggests that Lamin A/C expression could be involved in the organ tropism of tumor cells, thereby providing a rationale for further studies focused on the definition of cancer mechanism of metastatization.